(untitled) (Eurasian Journal of Learning and Academic Teaching, 2025)
The article identifies and substantiates the feasibility of using text in the process of forming communicative, linguistic, linguistic and cultural competences of schoolchildren; presents an analysis of the text as the highest unit of teaching speech activity; suggests criteria for selecting texts when teaching the native language; provides methodological recommendations for organizing the process of forming coherent speech of schoolchildren on a text basis.